Difference between revisions of "009B Sample Final 1, Problem 7"
Jump to navigation
Jump to search
(4 intermediate revisions by the same user not shown) | |||
Line 1: | Line 1: | ||
− | + | <span class="exam">(a) Find the length of the curve | |
− | + | ::<math>y=\ln (\cos x),~~~0\leq x \leq \frac{\pi}{3}</math>. | |
− | + | <span class="exam">(b) The curve | |
− | + | ::<math>y=1-x^2,~~~0\leq x \leq 1</math> | |
− | + | <span class="exam">is rotated about the <math style="vertical-align: -3px">y</math>-axis. Find the area of the resulting surface. | |
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | | | + | |'''1.''' The formula for the length <math style="vertical-align: 0px">L</math> of a curve <math style="vertical-align: -5px">y=f(x)</math> where <math style="vertical-align: -3px">a\leq x \leq b</math> is |
|- | |- | ||
− | | | + | | |
+ | <math>L=\int_a^b \sqrt{1+\bigg(\frac{dy}{dx}\bigg)^2}~dx.</math> | ||
|- | |- | ||
− | | | + | |'''2.''' Recall |
− | |||
|- | |- | ||
− | | | + | | <math style="vertical-align: -14px">\int \sec x~dx=\ln|\sec(x)+\tan(x)|+C.</math> |
|- | |- | ||
− | |'''3.''' The surface area <math style="vertical-align: 0px">S</math> of a function <math style="vertical-align: -5px">y=f(x)</math> rotated about the <math style="vertical-align: -4px">y</math>-axis is given by | + | |'''3.''' The surface area <math style="vertical-align: 0px">S</math> of a function <math style="vertical-align: -5px">y=f(x)</math> rotated about the <math style="vertical-align: -4px">y</math>-axis is given by |
|- | |- | ||
| | | | ||
− | + | <math style="vertical-align: -13px">S=\int 2\pi x\,ds,</math> where <math style="vertical-align: -18px">ds=\sqrt{1+\bigg(\frac{dy}{dx}\bigg)^2}~dx.</math> | |
|} | |} | ||
+ | |||
'''Solution:''' | '''Solution:''' | ||
Line 34: | Line 35: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |First, we calculate& | + | |First, we calculate <math>\frac{dy}{dx}.</math> |
|- | |- | ||
− | |Since <math style="vertical-align: - | + | |Since <math style="vertical-align: -5px">y=\ln (\cos x),</math> |
+ | |- | ||
+ | | <math>\frac{dy}{dx}=\frac{1}{\cos x}(-\sin x)=-\tan x.</math> | ||
|- | |- | ||
|Using the formula given in the Foundations section, we have | |Using the formula given in the Foundations section, we have | ||
|- | |- | ||
| | | | ||
− | + | <math>L=\int_0^{\pi/3} \sqrt{1+(-\tan x)^2}~dx.</math> | |
|} | |} | ||
Line 47: | Line 50: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now, we have | + | |Now, we have |
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
L & = & \displaystyle{\int_0^{\pi/3} \sqrt{1+\tan^2 x}~dx}\\ | L & = & \displaystyle{\int_0^{\pi/3} \sqrt{1+\tan^2 x}~dx}\\ | ||
&&\\ | &&\\ | ||
Line 67: | Line 70: | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
L& = & \ln |\sec x+\tan x|\bigg|_0^{\frac{\pi}{3}}\\ | L& = & \ln |\sec x+\tan x|\bigg|_0^{\frac{\pi}{3}}\\ | ||
&&\\ | &&\\ | ||
Line 85: | Line 88: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |We start by calculating& | + | |We start by calculating <math>\frac{dy}{dx}.</math> |
|- | |- | ||
− | |Since <math style="vertical-align: - | + | |Since <math style="vertical-align: -5px">y=1-x^2,</math> |
+ | |- | ||
+ | | <math>\frac{dy}{dx}=-2x.</math> | ||
|- | |- | ||
|Using the formula given in the Foundations section, we have | |Using the formula given in the Foundations section, we have | ||
|- | |- | ||
| | | | ||
− | + | <math>S\,=\,\int_0^{1}2\pi x \sqrt{1+(-2x)^2}~dx.</math> | |
|} | |} | ||
Line 98: | Line 103: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now, we have <math style="vertical-align: -14px">S=\int_0^{1}2\pi x \sqrt{1+4x^2}~dx.</math> | + | |Now, we have <math style="vertical-align: -14px">S=\int_0^{1}2\pi x \sqrt{1+4x^2}~dx.</math> |
|- | |- | ||
− | |We proceed by | + | |We proceed by <math>u</math>-substitution. |
|- | |- | ||
− | | | + | |Let <math style="vertical-align: -2px">u=1+4x^2.</math> |
|- | |- | ||
− | | | + | |Then, <math style="vertical-align: 0px">du=8xdx</math> and <math style="vertical-align: -14px">\frac{du}{8}=xdx.</math> |
− | + | |- | |
− | + | |Since the integral is a definite integral, we need to change the bounds of integration. | |
− | + | |- | |
− | + | |Plugging in our values into the equation <math style="vertical-align: -4px">u=1+4x^2,</math> we get | |
− | |||
− | | | ||
− | |||
− | |||
− | |||
|- | |- | ||
− | | | + | | <math style="vertical-align: -5px">u_1=1+4(0)^2=1</math> and <math style="vertical-align: -5px">u_2=1+4(1)^2=5.</math> |
|- | |- | ||
− | | | + | |Thus, the integral becomes |
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
− | + | S& = & \displaystyle{\int_1^5 \frac{2\pi}{8} \sqrt{u}~du}\\ | |
&&\\ | &&\\ | ||
− | & = & \displaystyle{\frac{\pi}{ | + | & = & \displaystyle{\frac{\pi}{4} \int_1^5 u^{\frac{1}{2}}~du.} |
− | |||
− | |||
− | |||
− | |||
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | !Step | + | !Step 3: |
|- | |- | ||
− | | | + | |Now, we integrate to get |
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
− | S & = & \displaystyle{\ | + | \displaystyle{S} & = & \displaystyle{\frac{\pi}{4}\bigg(\frac{2}{3}u^{\frac{3}{2}}\bigg)\bigg|_{1}^{5}}\\ |
&&\\ | &&\\ | ||
− | & = & \displaystyle{\frac{\pi}{6} | + | & = & \displaystyle{\frac{\pi}{6}u^{\frac{3}{2}}\bigg|_{1}^{5}}\\ |
&&\\ | &&\\ | ||
− | & = & \displaystyle{\frac{\pi( | + | & = & \displaystyle{\frac{\pi}{6}(5)^{\frac{3}{2}}-\frac{\pi}{6}(1)^{\frac{3}{2}}}\\ |
&&\\ | &&\\ | ||
& = & \displaystyle{\frac{\pi}{6}(5\sqrt{5}-1)}.\\ | & = & \displaystyle{\frac{\pi}{6}(5\sqrt{5}-1)}.\\ | ||
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
+ | |||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | |'''(a)''' <math>\ln (2+\sqrt{3})</math> | + | | '''(a)''' <math>\ln (2+\sqrt{3})</math> |
|- | |- | ||
− | |'''(b)''' <math>\frac{\pi}{6}(5\sqrt{5}-1)</math> | + | | '''(b)''' <math>\frac{\pi}{6}(5\sqrt{5}-1)</math> |
|} | |} | ||
[[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] | [[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] |
Latest revision as of 17:06, 20 May 2017
(a) Find the length of the curve
- .
(b) The curve
is rotated about the -axis. Find the area of the resulting surface.
Foundations: |
---|
1. The formula for the length of a curve where is |
|
2. Recall |
3. The surface area of a function rotated about the -axis is given by |
where |
Solution:
(a)
Step 1: |
---|
First, we calculate |
Since |
Using the formula given in the Foundations section, we have |
|
Step 2: |
---|
Now, we have |
|
Step 3: |
---|
Finally, |
|
(b)
Step 1: |
---|
We start by calculating |
Since |
Using the formula given in the Foundations section, we have |
|
Step 2: |
---|
Now, we have |
We proceed by -substitution. |
Let |
Then, and |
Since the integral is a definite integral, we need to change the bounds of integration. |
Plugging in our values into the equation we get |
and |
Thus, the integral becomes |
|
Step 3: |
---|
Now, we integrate to get |
|
Final Answer: |
---|
(a) |
(b) |